Média das medidas palpebrais em descendentes de orientais - Pamplona, André Luis Ferreira [UNIFESP] (2000)
Purpose: To determine average anatomical measurements in oriental offspring (both parents Japanese) aiming to help oculoplastic surgeons to deal with these patients. Methods: The palpebral crease height, eyebrow height and visible pretarsal skin were measured in 56 oriental offs-pring, totalizing 112 lids. 16 (28.5%) patients were male and 40 (71.5%) female. The mean age was 25.2 years. There were no statistically significant differences between right and left lids of both genders. Results: The average measure of the eyebrow height was 13.6 mm (2.5 SD) in males and 14.5mm (2.2 SD) in females. (T= 1.7) (P= 0.083), not statistically significant. The average of visible pretarsal skin in males was 1.2 (1.2 SD) and 1.7 (1.6 SD) in female. (T= 1.84) (P= 0.070), not statistically significant. The average palpebral crease height was 3.9 mm (2.5 SD) in males and 4.9 mm (2.9 SD) in females. (T= 1.95) (P= 0.060), not statistically significant. Conclusions: Due to equivalence of means between both lids and between both genders, the average measure- ments may be used as good anatomical marks in surgical procedures in Oriental lids.